PENYULUHAN TENTANG PENCEGAHAN PENULARAN COVID 19 DENGAN MEDIA BROSUR DAN POSTER DI AREA MESJID DESA SIHOPUR KECAMATAN ANGKOLA SELATAN TAPANULI SELATAN TAHUN 2020 - Ritonga, Nefonavratilova; Siregar, Nurelilasari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Covid-19 is a disease caused by a new type of corona virus that appeared at the end of 2019 for the first time in Wuhan, China which is currently causing a pandemic in almost all over the world. In an effort to prevent the increasingly widespread transmission of Covid-19. The government urges all levels of society to take various preventive steps such as carrying out physical distancing, using masks, washing hands regularly, increasing endurance and maintaining health. The counseling activity for Covid 19 prevention efforts in the mosque area aims to increase knowledge and change the behavior of the community, especially mosque congregants so that they can continue to make efforts to prevent the transmission of Covid 19 during the 5 daily prayers and tarawih and tadarusan prayers which are held in mosques during this month of Ramadan. This activity consisted of some counseling and distribution of brochures and leaflets to mosque nazir and mosque congregations. The results of the evaluation during the activity process were obtained that 90% (19 participants) experienced an increase in knowledge related to efforts to prevent Covid 19. With this counseling, it is hoped that it will be able to increase the knowledge and behavior of the community to always make efforts to prevent Covid 19 in any activity.